# `f(x)=xsqrt(3-x)` domain, end behavior, y-intercept, x-intercepts, graph it

### 1 Answer | Add Yours

`f(x) = xsqrt(3-x)`

(A) Domain of the function

Note that in square roots, a negative radicand is not allowed.

So to determine the domain, consider 3-x and set it greater than and equal to zero.

`3-x gt=0`

Then, solve for x. To do so, subtract both sides by 3.

`3-3-xgt=0-3`

`-xgt=-3`

And, divide both sides by -1.

`(-x)/(-1) gt=(-3)/(-1)`

Since the x changes from negative to positive, reverse the inequality.

`xlt=3`

**Hence, the domain of the given function is `(-oo, 3]` .**

(B) End behavior

To determine the end behavior of the function, consider its domain.

Since the domain is `(-oo, 3]` , to get the left end behavior of the function, take the limit of f(x) as it approaches negative infinity.

`lim_(x->-oo)f(x)=lim_(x->-oo) xsqrt(3-x) = -oo*sqrt(3-(-oo))`

Note that if a number is being multiplied to a very large negative number, the product is a very large negative number.

So,

`lim_(x->-oo)f(x)=-oo`

And to get the right end behavior, take the limit of f(x) as it approaches 3.

`lim_(x->3)f(x)=lim_(x->3) xsqrt(3-x) =3sqrt(3-3)=3*0=0`

**Hence, as x approaches negative infinity, f(x) approaches negative infinity. And as x approaches 3, f(x) approaches zero. Graphically, the left end of the graph goes down without bound and its right end stops at (3,0).**

(C) y-intercept

To solve, set x=0. Then, plug-in this value of x to the function.

`f(x) =xsqrt(3-x)`

`y=xsqrt(3-x)=0*sqrt(3-0)=0*sqrt3=0`

**Hence, the y-intercept is `(0,0)` .**

(D) x-intercept

To solve for x-intercept, set y=0.

`y=xsqrt(3-x)`

`0=xsqrt(3-x)`

Then, set each factor equal to zero.

For the first factor:

`x= 0`

And for the second factor:

`sqrt(3-x)=0`

Square both sides.

`(sqrt(3-x))^2=0^2`

`3-x=0`

And, add both sides by x.

`3-x+x=0+x`

`3=x`

**Hence, the x-intercepts are `(0,0)` and `(3,0)` .**

(E) Graph.

The graph of the given function is :